Case Report: Compound Heterozygous Variants of SLC13A3 Identified in a Chinese Patient With Acute Reversible Leukoencephalopathy and α-Ketoglutarate Accumulation - Kang, Qingyun; Yang, Liming; Liao, Hongmei; Yang, Sai; Yang, Haiyang; Ning, Zeshu; Liao, Caishi; Wu, Liwen (Frontiers in Pediatrics, 2021)
Abstract Background: SLC13A3 gene encodes the Na+/dicarboxylate cotransporter 3 (NaDC3), which locates on the plasma membrane and is mainly expressed in kidney, astrocytes and the choroid plexus. It imports four to six carbon dicarboxylates together with three Na+ ions into the cytosol. Nowadays, pathogenic variants of SLC13A3 gene were found to cause acute reversible leukoencephalopathy and α-ketoglutarate accumulation (ARLIAK) in patients. Here, we report two novel SLC13A3 variants c.331C>T (p.T62M) and c.185C>T (p.R111*) identified in a Chinese patient with ARLIAK. Case presentation: The patient was a Chinese girl aged 13 years and 7 months old, who had acute, recurrent neurological deterioration during two febrile episodes. She presented with reversible leukoencephalopathy and increased urinary excretion of α-ketoglutarate. Genetic studies revealed compound heterozygous variants (c.331C>T, p.T62M and c.185C>T, p.R111*) in SLC13A3, which had not been reported previously. Conclusions: These findings expand the variant spectrum of SLC13A3, providing the basis for the further study of this rare disease.